Introduction to environmental engineering - Davis, Mackenzie L. (McGraw-Hill, 2013)
Introduction to Environmental Engineering, 5/e contains the fundamental science and engineering principles needed for introductory courses and used as the basis for more advanced courses in environmental engineering. Updated with latest EPA regulations, Davis and Cornwell apply the concepts of sustainability and materials and energy balance as a means of understanding and solving environmental engineering issues. With over 720 end-of-chapter problems, as well as provocative discussion questions, and a helpful list of review items found at the end of each chapter, the text is both a comprehensible and comprehensive tool for any environmental engineering course. Standards and Laws are the most current and up-to-date for an environmental engineering text.